Diagnósticos de enfermagem em crianças hospitalizadas - Thayane Alves Moura César Lopes; Maria de Fátima Vasques Monteiro; Joseph Dimas de Oliveira; Dayanne Rakelly de Oliveira; Ana Karina Bezerra Pinheiro; Simone Soares Damasceno (Universidade Federal do Ceará, 2017)
Objective: to describe the frequency of nursing diagnoses in hospitalized children. Methods: this is a crosssectional study carried out in a hospital for children, from 738 medical records. Data analysis was based on descriptive statistics. Results: a frequency of 2,100 nursing diagnoses was identified, distributed in 15 diagnostic concepts, six domains, and 12 classes, according to NANDA-I Taxonomy II. The most prevalent diagnoses were: ineffective respiratory pattern (18.7%), hyperthermia (15.2%), impaired sleep pattern (11.1%), unbalanced nutrition: less than body needs (10.8%), fear (9.3%), acute pain (7.1%) and diarrhea (6.7%). Conclusion: five nursing diagnoses were described in hospitalized children: "ineffective respiratory pattern", "hyperthermia", "diarrhea", "fear" and "acute pain". The first three diagnoses are closely related to the conditions that determine the major causes of hospitalization in childhood: acute respiratory infections and gastroenteritis.